Anti-Theft Application for Android-Based Smartphone - Sandy Darmowinoto; Seno Hadi Wibowo (President University, 2016)
— In daily life, almost everyone uses smart phone with different types of operating system and one of them is android. People intention to steal someone else smartphone were very high. This is one of the problems for all Android smart phone users. While it was happening, they could not do anything to get it back. The objective of this research is to create an application that will help android smart phone users to get information about their phone. The information will be obtained by the user which is about the location of their android smart phones. Another feature, it can lock android smart phone while the SIM changed by other person. Only one registered SIM card that can access the android smart phone. Last thing, their phone can be checked by the trigger alarm feature. Those features can be obtained by sending the keywords via SMS remotely from another phone user. This application needs two devices in order to run perfectly as this application runs remotely by another device. Also, these applications need enough amount of pulse to send the keywords. It needs GPS and network connection to obtain the right location. This application will make the android smart phone users feel safe, secure, and comfortable and not have to worry about their phone.